Selective Reduction of Carbonyl Compounds via (Asymmetric) Transfer Hydrogenation on Heterogeneous Catalysts - Baráth, Eszter (Synthesis, 2020)
Based on the ever-increasing demand for optically pure compounds, the development of efficient methods to produce such products is very important. Homogeneous asymmetric catalysis occupies a prominent position in the ranking of chemical transformations, with transition metals coordinated to chiral ligands being applied extensively for this purpose. However, heterogeneous catalysts have the ability to further extend the field of asymmetric transformations, because of their beneficial properties such as high stability, ease of separation and regeneration, and the possibility to apply them in continuous processes. The main challenge is to find potential synthetic routes that can provide a chemically and thermally stable heterogeneous catalyst having the necessary chiral information, whilst keeping the catalytic activity and enantioselectivity equally high (or even higher) than the corresponding homogeneous counterpart. Within this short review, the most relevant immobilization modes and preparative strategies depending on the support material used are summarized. From the reaction scope viewpoint, metal catalysts supported on the various solid materials studied in (asymmetric) transfer hydrogenation of carbonyl compounds are selected and represent the main focus of the second part of this overview.1 Introduction2 Synthesis of Chiral Heterogeneous Catalysts2.1 Immobilization of Homogeneous Asymmetric Catalysts2.1.1 Immobilization on Inorganic Supports2.1.2 Immobilization on Organic Polymers as Supports2.1.3 Immobilization on Dendrimer-Type Materials as Supports2.1.4 Self-Supported Chiral Catalysts: Coordination Polymers2.1.5 Immobilization Using Non-Conventional Media2.2 Chirally Modified Metal Surfaces for Heterogeneous Asymmetric Catalysis3 Examples of Transfer Hydrogenation on Heterogeneous Catalysts3.1 Silicon-Immobilized Catalysts3.2 Carbon-Material-Immobilized Catalysts3.3 Polymer-Immobilized Catalysts3.4 Magnetic-Nanoparticle-Immobilized Catalysts4 Conclusions
Keywords: transfer hydrogenation; asymmetric transfer hydrogenation; asymmetric catalysis; carbonyl compounds; immobilization; heterogeneous catalysis; solid supports